Profile of romosozumab and its potential in the management of osteoporosis - Lim SY; Bolster MB (Dove Medical Press, 2017)
Sian Yik Lim,1 Marcy B Bolster2 1Straub Bone & Joint Center, Straub Medical Center, Honolulu, HI, 2Division of Rheumatology, Allergy & Immunology, Massachusetts General Hospital, Harvard Medical School, Boston, MA, USA Abstract: Increased understanding of bone biology has led to the discovery of several unique signaling pathways that regulate bone formation and resorption. The Wnt signaling pathway plays a significant role in skeletal development, adult skeletal homeostasis, and bone remodeling. Sclerostin is an inhibitor of the Wnt signaling pathway. Romosozumab, a humanized monoclonal antibody that binds to sclerostin, prevents sclerostin from exerting this inhibitory effect. Therefore, in the presence of romosozumab, the Wnt signaling pathway is activated leading to bone formation and bone mineral density gain. Clinical studies of romosozumab have shown that this agent is one of the most potent bone anabolic agents in development to date. Romosozumab does not act solely as an anabolic agent, but rather, it has effects on increasing bone formation as well as reducing bone resorption. In the clinical studies, patients tolerated romosozumab well with no major safety signals reported. In a Phase III study, romosozumab as compared to placebo has been shown to reduce vertebral fractures by 73% after 1 year of treatment. Sequential therapy with romosozumab for 1 year followed by denosumab in the second year reduced vertebral fractures by 75% as compared to the group that received placebo for 1 year and denosumab in the second year. Romosozumab holds significant potential, by a novel mechanism of action, to expand our ability to treat osteoporosis. More studies are needed to determine the ideal setting in which romosozumab may be used to optimize osteoporosis treatment. Keywords: romosozumab, sclerostin, osteoporosis, bone mineral density